STAT4 but not TRAF1/C5 variants influence the risk of developing rheumatoid arthritis and systemic lupus erythematosus in Colombians (2008)
The aim of this study was to determine the influence of STAT4 (rs7574865) and TRAF1/C5 (rs10818488 and rs2900180) gene polymorphisms on the risk of developing rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE) in a Colombian population. This was a case-control study in which 839 individuals with RA (N = 274) and SLE (N = 144) and matched healthy controls (N = 421) were included. Genotyping was performed by using a polymerase chain reaction system with pre-developed TaqMan allelic discrimination assay. STAT4 rs7574865T allele disclosed a significant influence on the risk of developing SLE (P = 0.0005; OR 1.62, 95% CI 1.22-2.16) and RA (P = 0.008; OR 1.36; 95% CI 1.08-1.71), whereas no effect on these autoimmune diseases was observed for the TRAF1/C5 polymorphisms examined. Our data strengthen STAT4 rs7574865 polymorphism as a susceptibility factor for RA and SLE and provide further evidence for a common origin of autoimmune diseases.